2023
DOI: 10.1186/s13102-023-00726-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between tibial torsion, knee flexion excursion and foot progression during gait in people with knee osteoarthritis: a cross-sectional study

Chen Huang,
Ping-Keung Chan,
Kwong-Yuen Chiu
et al.

Abstract: Background Lower limb malalignment is associated with gait kinematics, but there is limited information on the relationship between gait kinematics and tibial torsion in individuals with knee osteoarthritis (OA). This study aimed to investigate possible associations between tibial torsion and early stance kinematics during gait in people with mild and moderate medial knee OA. Methods Forty-seven participants (age: 62.1 ± 6.0 years; female/male: 37/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Yoon & Shin [ 31 ] reported that among female OA patients, those with wider step width showed greater foot progression angles. In addition, a recent study reported that external tibial torsion was related to external foot progression [ 35 ], but it is difficult to compare because external tibial torsion as one of our study limitations is not measured in this study.…”
Section: Discussionmentioning
confidence: 96%
“…Yoon & Shin [ 31 ] reported that among female OA patients, those with wider step width showed greater foot progression angles. In addition, a recent study reported that external tibial torsion was related to external foot progression [ 35 ], but it is difficult to compare because external tibial torsion as one of our study limitations is not measured in this study.…”
Section: Discussionmentioning
confidence: 96%
“…They postulated that this relationship is a result of nature trying to restore the extension-to-flexion change in joint line obliquity, thus making the joint line parallel to the ground in a flexed knee. In order to maintain a normal foot progression angle with increased internal femoral torsion, a compensatory external rotation of the tibia may reduce the external knee’s adduction moment [ 46 ]. Increased femoral neck anteversion also shifts the mechanical axis towards valgus and decreases the stress across the medial compartment [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%